Efficiency of endovascular revascularization in patients with chronic heart failure with reduced left ventricular ejection fraction and diabetes mellitus according to a five-year observation. (14th October 2021) - Svarovskaya, A; Garganeeva, A.A
Abstract: Purpose: The purpose of the study was to evaluate the effect of endovascular coronary revascularization in patients with coronary heart disease (CHD) complicated by chronic heart failure (CHF) with reduced left ventricular ejection fraction (LVEF) and comorbid with type 2 diabetes mellitus (DM) according to a five-year prospective follow-up. Material and methods: The study included a total of 83 patients with coronary artery disease with CHF functional class (FC) II-III according to NYHA and LVEF less than 40% aged 48 to 58 years. Group 1 (n=38) included patients with CHD without DM; group 2 comprised 45 patients with CHD associated with DM. The endpoint was one of the adverse cardiovascular events (CVE) (death, nonfatal myocardial infarction, acute coronary syndrome, stroke, stent restenosis, CHF progression by 1 FC or more, repeated coronary revascularization (surgical, endovascular), development of ventricular arrhythmia, atrial fibrillation, and implantation of a pacemaker) occurring within five years of observation. Results: One year after endovascular intervention, LVEF increased by 10.3% (p=0.05) in group 1 and by 13.4% (p=0.05) in group 2. The LVEF values in DM patients decreased by 9.5% after three years of observation. Manifestation of CHF occurred by 4.6 and 3.7 times less frequently in patients of group 1 after one and three years, respectively, compared with that in DM patients. After five years, 15.4% of patients in group 2 and none in group 1 (p=0.006) required hospitalizations for CHF progression. After three years, repeated interventions were required twice more often in group 2 (p=0.041). After five years, no repeated interventions were performed in group 1 whereas 30.8% of patients in group 2 received repeated interventions (p=0.011). One year after coronary artery stenting, the Kaplan-Meier survival rates were 91.3% in group 1 and 93.3% in group 2. The study showed that the survival curves significantly (p=0.020) diverged after three years of observation and by the end of the fifth year (p=0.011). The study showed that smoking (odds ratio (OR) 3.861, p=0.01) and the level of postprandial glycemia (OR 2.622; p=0.01) were predictors for the development of unfavorable factors. Evaluation of DM course showed that patients with episodes of hypoglycemia were significantly more frequently diagnosed with onset of new unfavorable CVE including progression of atherosclerosis in the native coronary arteries (p=0.05) and, later, CHF decompensation (p=0.004–0.04). Findings: The annual results were comparable between study groups. Assessment of results from three-year follow-up showed that patients with DM and CHF who underwent endovascular revascularization had a significantly lower survival rate and a higher need for repeated revascularization. The five-year survival rate was significantly lower in group of DM patients (p=0.011). Funding Acknowledgement: Type of funding sources: None.